KONSEP DIRI PROFESIONALISME MUDA (Studi Kasus: 5 Orang Profesionalisme Muda di Kota Pekanbaru) - Rohadatul Aisy; Swis Tantoro (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This study aims to find out and analyze how the performance of a young person who already has a job and is able to be professional in working. This research was conducted in Pekanbaru City because it is a metropolitan city and has a high number of workers. This type of research is qualitative descriptive by using observation, interview and documentation techniques. In determining the subject of research using purposive sampling technique that is predetermined based on criteria. The number of informants from this study were 5 people. The theory used is the self-concept of Mead and the lifestyle of Baudlliard. The results of the research found by researchers were that a young worker in order to have a professional attitude must have a mature self-concept. The mature self concept found by researchers is that the informant has a plan for the future, understands the strengths and weaknesses that exist in him, and is able to adjust himself to what he is facing. As a young person who already has his own income and lives in a modern era with a high consumptive pattern, the informants found by researchers have a modern lifestyle with characteristics that are like hanging out and shopping for needs that prioritize brands rather than quality, although there are some informants who do not prioritizing brand but also quality. In this study it was found that workers must be able to distinguish attitudes and ways of interacting between fellow coworkers and their daily environment. Professionalism is needed in work because according to informants in this study, they will feel very satisfied when they have worked hard and will affect the relationship between the boss and employees.Keywords: Professionalism, Young Workers, Self Concept